NeoAPACHE II. Relationship Between Radiographic Pulmonary Area and Pulmonary Hypertension, Mortality, and Hernia Recurrence in Newborns With CDH - Amodeo, Ilaria; Pesenti, Nicola; Raffaeli, Genny; Macchini, Francesco; Condò, Valentina; Borzani, Irene; Persico, Nicola; Fabietti, Isabella; Bischetti, Giulia; Colli, Anna Maria; Ghirardello, Stefano; Gangi, Silvana; et al. (Frontiers in Pediatrics, 2021)
Congenital diaphragmatic hernia is a rare disease with high mortality and morbidity due to pulmonary hypoplasia and pulmonary hypertension. The aim of the study is to investigate the relationship between radiographic lung area and systolic pulmonary artery pressure (sPAP) on the first day of life, mortality, and hernia recurrence during the first year of life in infants with a congenital diaphragmatic hernia (CDH). A retrospective data collection was performed on 77 CDH newborns. Echocardiographic sPAP value, deaths, and recurrence cases were recorded. Lung area was calculated by tracing the lung’s perimeter, excluding mediastinal structures and herniated organs, on the preoperative chest X-ray performed within 24 hours after birth. Logistic and linear regression analyses were performed. Deceased infants showed lower areas and higher sPAP values. One cm2 of rising in the total, ipsilateral, and contralateral area was associated with a 22%, 43%, and 24% reduction in mortality risk. sPAP values showed a decreasing trend after birth, with a maximum of 1.84 mmHg reduction per unitary increment in the ipsilateral area at birth. Recurrence patients showed lower areas, with recurrence risk decreasing by 14% and 29% per unit increment of the total and ipsilateral area. In CDH patients, low lung area at birth reflects impaired lung development and defect size, being associated with increased sPAP values, mortality, and recurrence risk. Clinical Trial Registration: The manuscript is an exploratory secondary analysis of the trial registered at ClinicalTrials.gov with identifier NCT04396028.